Exclusive enteral nutrition for induction of remission in anti-tumor necrosis factor refractory adult Crohn’s disease: the Indian experience - Sood, Ajit (Intest Res, 2020)
BACKGROUND/AIMS: Exclusive enteral nutrition (EEN) is recommended for induction of remission in pediatric Crohn’s disease (CD). However, it is not currently recommended for inducing remission in adults. This report describes the use of 12-week EEN for induction of remission in anti-tumor necrosis factor (anti-TNF) refractory adult CD. METHODS: This is a retrospective analysis of adults with moderate to severe active (Crohn’s Disease Activity Index [CDAI] >220) anti-TNF refractory CD, who received EEN for 12 weeks between April 2018 and March 2019 at Dayanand Medical College and Hospital, Ludhiana, India. Primary outcomes included achievement of clinical remission and fistula healing at 12 weeks. Improvement in inflammatory markers and nutritional status were the secondary end points. RESULTS: Out of 23 patients who received anti-TNF agents, 7 (30.4%) were refractory and were offered EEN as a salvage therapy. Six patients (66.7% females, mean age 25.6±6.5 years) consented. Four patients (66.6%) achieved clinical remission (CDAI <150). Mean CDAI of patients decreased significantly after 12 weeks of EEN (388.8±74.8 vs. 160.0±25.2, P<0.001). Perianal fistulas showed clinical response (drainage decreased by >50%), though none achieved remission. Entero-enteric fistulae showed complete healing. Mean body mass index improved from 15.6±3.1 to 18.9±1.9 kg/m(2) at week 12 (P=0.003). Hemoglobin and serum albumin also improved from 8.2±1.1 g/dL and 2.8±0.3 g/dL at baseline to 12.6±0.6 g/dL and 3.6±0.5 g/dL post-EEN respectively (P<0.001 and P=0.006 respectively). CONCLUSIONS: EEN appears to be an effective and well tolerated therapy for induction of remission in anti-TNF refractory adult CD. More data from prospective trials with larger number of patients is required.